STUDY ON ENVIRONMENTAL COSTS: AN APPROACH TO ENVIRONMENTAL MANAGEMENT ACCOUNTING (EMA) - Sihar Tigor Benjamin Tambunan (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2012)
Regarding to environmental management accounting context, here in after referred to as EMA (Environmental Management Accounting), waste is the part of the production output. It has to absorb various types of costs (direct or indirect) such as a real product. The condition also well explained in a statement that the environmental costs of a production system is actually larger than is conventionally estimated by several companies over the years, that is identical to the cost of environmental costs incurred by the company to remove waste from the production system. The use of diagrams Material & Energy Flow Accounting (MEFA) is recommended in this EMA approach to simplify the process of tracking the flow of environmental costs in each production process. Assuming that there is no conditions of 100% efficiency in a production system, the presence of waste production is an inefficient symptom that will occur yet may be minimized.